Green House Gas Emissions from Motor Vehicles in Urban Indonesia: Systematic Literature Review 2015-2025 - Mahdiah, Intan; Akhsan, Hamdi; Maliya, Fina; Murniati, Murniati (Kappa Journal, 2026)
The transportation sector on land in Indonesia is responsible for about 27% of the country's total greenhouse gas emissions, which has a big effect on global warming (KLHK, 2021; WRI Indonesia, 2024). This study looks at trends in vehicle emissions, the main ways emissions are measured, and where more research is needed. It uses a Systematic Literature Review (SLR) method based on the PRISMA 2020 guidelines. The research searched five major databases: Scopus, ScienceDirect, Google Scholar, Portal Garuda, and Sinta, covering the time from January 1, 2015, to December 31, 2025. Out of 512 records found, 26 articles were included after going through a careful selection process. The results show that the number of cars owned increased by about 7–8% each year from 2015 to 2019, and this rate went up to 10–12% every year between 2021 and 2025 after the pandemic. By April 2025, the total number of vehicles in the country was around 168 million, with motorcycles making up most of that number, between 139 and 157 million. Most studies used the bottom-up method (69% of them), and most empirical research was done in Jakarta (14 articles), Surabaya (8 articles), and Bandung (4 articles). Medium-sized cities like Palembang, Medan, and Makassar have not been studied much and are considered scientific blind spots. In 2025, the transportation sector is expected to account for about 24.63% of the country's greenhouse gas emissions in 2024 and might rise to 28% of total carbon emissions from transport. During the dry season, urban areas have air pollution levels that are 42–57% from motor vehicles. More research in these cities is needed to help Indonesia reach its 2030 Nationally Determined Contribution (NDC) goals. This includes making better emission inventories and looking at possible ways to reduce emissions, such as switching to low-emission vehicles, which could help avoid up to 170 million tons of carbon emissions by 2040.